Beyond Peptides and Peptidomimetics: Natural Heteroaromatic Amino Acids in the Synthesis of Fused Heterocyclic Frameworks for Bioactive Agents - Isis Apolo Silveira de Borba; Jamile Buligon Peripolli; Angélica Rocha Joaquim; Fernando Fumagalli (Organics)
Heterocycle cores are widely used in medicinal chemistry for developing bioactive compounds. In this scenario, using cheap and accessible starting material to build these heterocycles is desirable to obtain new drug candidates for cost-efficient processes. One easily accessible source of starting material are amino acids. Usually, these compounds are employed in peptide synthesis, but their use for building heterocycle frameworks presents another appealing opportunity. Therefore, this review highlights the application of histidine and tryptophan, two heteroaromatic amino acids, in fused heterocyclic scaffold synthesis and their use in bioactive compounds.